<span>4(3-2x)=22
4(3) - 4(2x) = 22
12 - 8x = 22
8x = 12 - 22
8x = -10
x = -10/8 = -5/4
or
x = -1.25</span>
Let's solve your equation step-by-step.<span><span>−<span>5<span>(<span>x−4</span>)</span></span></span>=<span>−<span>30
</span></span></span>Step 1: Simplify both sides of the equation.<span><span>−<span>5<span>(<span>x−4</span>)</span></span></span>=<span>−30</span></span>
<span>Simplify: (Show steps)</span><span><span><span>−<span>5x</span></span>+20</span>=<span>−<span>30
</span></span></span>Step 2: Subtract 20 from both sides.<span><span><span><span>−<span>5x</span></span>+20</span>−20</span>=<span><span>−30</span>−20</span></span><span><span>−<span>5x</span></span>=<span>−<span>50
</span></span></span>Step 3: Divide both sides by -5.<span><span><span>−<span>5x</span></span><span>−5</span></span>=<span><span>−50</span><span>−5</span></span></span><span>x=<span>10
</span></span>Answer:<span>x=<span>10</span></span>
25 is the length of x, using the 30-60-90 special triangle method
(0,6) is on the y-axis. (5,-2) is on the 4th quadrant. (-1,10) is on the 2nd quadrant. (-1/4, -6*1/2) is on the 3rd quadrant. (5,0) is on the x axis. (8.7,2.3) is on the 1rst quadrant
9...
75 + 6 = 81
The square root of 81 = 9